Host nectin-1 is required for efficient Chlamydia trachomatis serovar E development - Hall, Jennifer V.; Sun, Jingru; Slade, Jessica; Kintner, Jennifer; Bambino, Marissa; Whittimore, Judy; Schoborg, Robert V. (Frontiers in Cellular and Infection Microbiology, 2014)
Interaction of Herpes Simplex Virus (HSV) glycoprotein D (gD) with the host cell surface during Chlamydia trachomatis/HSV co-infection stimulates chlamydiae to become persistent. During viral entry, gD interacts with one of 4 host co-receptors: HVEM (herpes virus entry mediator), nectin-1, nectin-2 and 3-O-sulfated heparan sulfate. HVEM and nectin-1 are high-affinity entry receptors for both HSV-1 and HSV-2. Nectin-2 mediates HSV-2 entry but is inactive for HSV-1, while 3-O-sulfated heparan sulfate facilitates HSV-1, but not HSV-2, entry. Western blot and RT-PCR analyses demonstrate that HeLa and HEC-1B cells express nectin-1 and nectin-2, but not HVEM. Because both HSV-1 and HSV-2 trigger persistence, these data suggest that nectin-1 is the most likely co-receptor involved. Co-infections with nectin-1 specific HSV-1 mutants stimulate chlamydial persistence, as evidenced by aberrant body (AB) formation and decreased production of elementary bodies (EBs). These data indicate that nectin-1 is involved in viral-induced chlamydial persistence. However, inhibition of signal transduction molecules associated with HSV attachment and entry does not rescue EB production during C. trachomatis/HSV-2 co-infection. HSV attachment also does not activate Cdc42 in HeLa cells, as would be expected with viral stimulated activation of nectin-1 signaling. Additionally, immunofluorescence assays confirm that HSV infection decreases nectin-1 expression. Together, these observations suggest that gD binding-induced loss of nectin-1 signaling negatively influences chlamydial growth. Chlamydial infection studies in nectin-1 knockdown (NKD) HeLa cell lines support this hypothesis. In NKD cells, chlamydial inclusions are smaller in size, contain ABs, and produce significantly fewer infectious EBs compared to C. trachomatis infection in control HeLa cells. Overall, the current study indicates that the actions of host molecule, nectin-1, are required for successful C. trachomatis development.